Nilai Sosial Dalam Cerpen Shabondama - Yuliani Rahmah (Diponegoro University, 2019)
Shabondama is one of Yoshio Toyoshima's short stories that tells the story of a magician named Havons. Havons who is not willing to die of his son trying to restore his son's life with the help of a witch who gave him magic bubbles. With these bubbles Havons traveled while showing his magic.By using literature study approach this article will describe the social values during Havons' journey. Through the characters action and conflict this short story tried to implies a message of kindness to the surrounding community as a social values. As result it can be understood that the characters in this short story teach social values that refer to services between people, togetherness in life and fair actions towards others. With these values Shabondama short story has a social function as a literary work that teaches something in an entertaining way.